Energy Potent Shortcut Tree Routing in Zigbee Networks - Rajeshkanna, B.; Anitha, M. (International Journal of Engineering and Technology, 2018)
ZigBee is an international standard for low-power and low-data rate WPAN. ZigBee works on IEEE 802.15.4 MAC and physical layers. Its network layer is liable to facilitate routing in networks. To provide a near optimal routing path as well as to balance the load and energy over the nodes, Energy-efficient shortcut tree routing (ESTR) protocol suggested an optimization method with three criteria such as minimum hop-counts, minimum congestion and maximum link quality. This paper proposes an Energy potent shortcut tree routing (EPSTR) that adds one more criterion called minimum failure-transmissions with EPSTRâ€™s criteria. The values for these criteria can be derived from the neighbor table data of a node. Performance evaluation reveals that EPSTR appreciably expands the network lifetime and shows better routing performances compared to ESTR.Â Â